Absence of Stress‐Induced Anisotropy During Brittle Deformation in Antigorite Serpentinite. Issue 12 (29th December 2018) - David, Emmanuel C.; Brantut, Nicolas; Hansen, Lars N.; Mitchell, Thomas M.
Abstract: Knowledge of the seismological signature of serpentinites during deformation is fundamental for interpreting seismic observations in subduction zones, but this has yet to be experimentally constrained. We measured compressional and shear wave velocities during brittle deformation in polycrystalline antigorite, at room temperature and varying confining pressures up to 150 MPa. Ultrasonic velocity measurements, at varying directions to the compression axis, were combined with mechanical measurements of axial and volumetric strain, during direct loading and cyclic loading triaxial deformation tests. An additional deformation experiment was conducted on a specimen of Westerly granite for comparison. At all confining pressures, brittle deformation in antigorite is associated with a spectacular absence of stress‐induced anisotropy and with no noticeable dependence of wave velocities on axial compressive stress, prior to rock failure. The strength of antigorite samples is comparable to that of granite, but the mechanical behavior is elastic up to high stress ( ≳ 80 % of rock strength) and nondilatant. Microcracking is only observed in antigorite specimens taken to failure and not in those loaded even at 90–95% of their compressive strength. Microcrack damage is extremely localized near the fault and consists of shear microcracks that form exclusively along the cleavage plane of antigorite crystals. Our observations demonstrate that brittle deformation in antigorite occurs entirely by "mode II" shear microcracking. This is all the more remarkable than the preexisting microcrack population in antigorite, is comparable to that in granite. The mechanical behavior and seismic signature of antigorite brittle deformation thus appears to be unique within crystalline rocks. Key Points: Brittle deformation in antigorite is not associated with any stress‐induced anisotropy Brittle deformation in antigorite is also not associated with any significant dilatancy up to failure Brittle deformation in antigorite is accomodated by extremely localized "mode II" shear microcracks